Microalgal Biofuels: A review - Meghnani, Roshni (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">Biofuels in this generation is the most important energy source as it plays a major role in environmental protection and sustainability. Microalgae, considered as a potential source of biofuel because of its high growth rate, consumes less water and is cost effective. Various types of biofuels are produced from microalgae such as biodiesel, bio-oil, bio hydrogen and bioethanol. Cultivation system of microalgae is considered as the major part in the biofuel production. Developments in the microalgal cultivation system can enhance the production and will be cost effective.